A Multiobjective Spatial-based Zone Design Model (MoSZoD) - Bong, Chin Wei; Chai, W.Y; Wong, C.W. (IEEE, 2005)
This paper presents a multiobjective approach for a spatial-based zone design model to the division of a land surface into two or more pieces. The model employs multiobjective optimization technique and Geographic Information System (GIS) as its components. This paper defines the problem based on multiobjective because it considers relationship among objectives and it is much more realistic to solve a real-world spatial zoning problem. The multiobjective decision analysis has been used to approximate and handle the Pareto-optimal solution to get optimal solution set after this paper applies a heuristic method to generate nondominated alternatives. This paper also aggregates the decision-makers' preferences by allowing interactivity with decision-makers. The flow of the model and its implementation in the GIS environment is presented. The computation has resulted in improvements in spatial zoning.